Hubungan Antara Petani Karet Dengan Toke (Patron-client) di Desa Teratak Kecamatan Rumbio Jaya Kabupapen Kampar - Refliana '; Novia Dewi; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the shape of the rubber marketing channels, costs, margins, profits and the relationship between the rubber farmers in the village Toke Teratak. This study uses survey and sampling techniques purposive sampling. The population in this study are 208 people with the number of farmers sampled as many as 24 people and 4 samples Toke appropriate criteria. More efficient marketing channels, namely, the marketing channel III. Marketing channel III total marketing costs are smaller and farmer's share (Part Farmers received) higher and lower marketing efficiency. The amount of marketing margin analysis contained in the marketing channel of rubber channel 1 and channel Toke In the third, amounting to Rp. 2,500/kg. Marketing efficiency is more efficient (smallest) obtained at the third marketing channel that is Rp. 6.08% with a marketing fee of Rp. 730/kg and the farmer received Rp. 83.33%. The relationship between farmers and the dominant Toke comes to accounts payable, so that farmers have a high dependence on Toke   Keyword: Marketing channels, Patron-Client, Rubber Farmer, Toke